A Study of Bronchoconstrictng Effect of Non Selective Beta Adrenergic Blocking Agent on Isolated Respiratory Smooth Muscle of Guinea-pig - Nawaz, Shah; Ahmed, Abdul Rashid; Ahmed, Qazi Rashid (Journal of Postgraduate Medical Institute, 2011)
Effect of a nonselective beta adrenergic blocking agent, propranolol, was observed on the isolated lung parenchymal strip of gunea-pig. Propranolol produced no effect on the tissue, showing that it has got no inherent kproperty of causing contraction of the tissue. Acety-choline, histamine and prostaglandin F2a produced dose related contraction of the tissue, but there was no significant change in the response of the tissue to these broncho-constricting agents in the presence of propranolol.